Age at Natural Menopause and Influencing Factors in Women Attending the Gynecological Outpatient Clinic at a Tertiary Care Hospital - Ali KY; Erkok U; Mohamed NA; Hilowle NM; Elmi HAH; Mohamud RYH (International Journal of Women's Health, 2023)
Khadija Yusuf Ali,1 Umut Erkok,1 Nur Adam Mohamed,2 Nasra Mohamud Hilowle,3 Hodan Abdi Hassan Elmi,1 Rahma Yusuf Haji Mohamud4 1Department of Obstetrics and Gynecology, Mogadishu Somalia Türkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 2Department of Psychiatry and Behavioral Sciences, Mogadishu Somalia Türkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 3Department Anesthesiology and Reanimation, Mogadishu Somali Turkey, Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia; 4Department of Education, Mogadishu Somalia Türkiye Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, SomaliaCorrespondence: Khadija Yusuf Ali, Mogadishu Somalia Türkiye Recep Tayyip Erdogan Research and Training Hospital, Department of Obstetrics and Gynecology, Mogadishu, Somalia, Email khadiijo13@hotmail.comBackground: Menopause is the irreversible cessation of menstruation that results from the lack of ovarian follicular function and is diagnosed after 12 consecutive months of amenorrhea without reasonable cause. This study aims to determine the average age at natural menopause and identify its associated factors among Somali women.Methods: This is a cross-sectional study conducted at the Mogadishu Somalia Türkiye Recep Tayyip Erdogan research and training hospital’s Obstetrics and Gynecology outpatient clinic between June 1 and July 1, 2023. Data was collected from subjects during the data collection period using face-to-face interviews with structured questionnaires consisting of sociodemographic, lifestyle, dietary, and reproductive characteristics. A multivariate logistic regression analysis was conducted to find the association between menopause age and target variables.Results: Out of the 188 participants recruited for the study, the median age of menopause was 45.00 (95% CI = 44.50– 45.62), and 48.9% had either premature or early menopause. The majority (53.7%) of the participants had a minimum of eight children. In Spearman’s rank correlation analysis, we found a significantly positive correlation between menopausal age and age at first (p< 0.01), last childbirth (p< 0.01), number of parities (p< 0.05), and age at marriage (p< 0.05). In multivariate logistic regression, we found that the odds of developing premature or early menopause among unemployed women were 59% lower than those of employed women (AOR = 0.41, 95% CI = 0.18– 0.93).Conclusion: In this study, we established that the age of natural menopause was lower than the findings reported by previous authors. We also found that employment status, education, history of contraceptive use, BMI, age at first and last childbirth, and parity were associated with age at natural menopause, suggesting that social, lifestyle, and reproductive factors may have an impact on menopausal age.Keywords: age at menopause, parity, associated factors, postmenopausal women, Somalia